APPLICATION OF NUCLEAR ANALYTICAL TECHNIQUES IN CHARACTERIZATION OF SEVERAL SAMPLE MATRICES - Diah D Lestiani; Muhayatun Santoso; S Kurniawati; E Damastuti; N Adventini; D K K Sari; I Kusmartini (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2020)
The existence of elements in major, minor, and even in trace levels could have a significant impact on human health, environmental, industry, or other life sciences. Results of characterization from several matrices of samples could become as valuable and important information since a lot of important decisions regarding public health, environmental protection, and international trade is based on those results. Characterization of several matrices of samples requires excellence, reliable, and complies with ideal criteria as an analytical method. In recent years, nuclear analytical techniques become one of the analytical techniques that could meet the challenge of capability in characterization various matrices of samples and have been proven to be suitable and applicable in a broad range of applications. Nuclear analytical techniques deal with nuclear excitations, electron inner-shell excitations, nuclear reactions, and/or nuclear decay. These techniques are selective with high sensitivity, non-destructive, simultaneous, and limit detection microgram until nanogram level. In this paper, the role and contribution of nuclear analytical techniques used for BATAN research, especially neutron activation analysis (NAA), particle-induced X-ray emission (PIXE), and X-ray Fluorescence (XRF) in the characterization of various matrices of geological, pharmacy, biology and environmental samples were discussed. The comparison with other methods was also carried out. The validations of results were conducted by analysis of standard reference material (SRM). Discussion related optimization of parameter measurement and similar efforts were also presented. The results of this research are hopefully could show and emphasize the significant role of NAT in the characterization of several matrices of samples in contribution and support the life sciences and public welfare.